Diabetic Cheiroarthropathy: A Recognised but Forgotten Complication—A Cross-Sectional Study Among Type 2 Diabetes Mellitus Patients in Seremban, Malaysia - Fithri, Zairul Nizam Z; Gnanou, Justin Vijay; Chandran, Shevaaliiny Ravi; Letchumenan, Shobna Sai; Ikram, Mohammad Arshad (Malaysian Journal of Medical Sciences, 2026)
Background: Diabetic cheiroarthropathy (DCA), or limited joint mobility, is a common yet underdiagnosed complication of diabetes, causing painless hand stiffness and reduced arm function. It is linked, among others, to small blood vessel damage, but local Malaysian data about this condition are scarce. This study aimed to ascertain DCA prevalence among patients with type II diabetes mellitus (DM) in Seremban, Malaysia, and to explore its effects on their daily function. Methods: A prospective, cross-sectional study was conducted from September 2024 to August 2025 at a primary healthcare clinic with 320 adults with type II DM. Patients with pre-existing hand problems were excluded. DCA was diagnosed using prayer and tabletop signs. The range of wrist movement was measured with a goniometer, and upper limb function was determined using the QuickDASH questionnaire. The data were analysed using logistic regression to find links between DCA and demographic and clinical characteristics. Results: Out of 320 patients, 43.8% had DCA. In the univariate analysis, older age and longer DM duration were linked to having DCA. In the multivariate regression, smoking and DM duration were better predictors of DCA. Patients with DCA had less wrist movement and worse arm function, as shown by lower wrist extension (71.9° vs. 75.9°) and higher QuickDASH scores (7.2 vs. 4.5), indicating more disability. Conclusion: DCA is a prevalent and clinically significant complication among type II DM patients in Malaysia, contributing to functional impairment. Longer DM duration and smoking may increase the risk of DCA. Regular screening using simple tests can help with the early detection and prevention of musculoskeletal complications among type II DM patients.